2012
DOI: 10.1002/jmr.1168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a high‐affinity human antibody with a disulfide bridge in the third complementarity‐determining region of the heavy chain

Abstract: Disulfide bridges are common in the antigen-binding site from sharks (new antigen receptor) and camels (single variable heavy-chain domain, VHH), in which they confer both structural diversity and domain stability. In human antibodies, cysteine residues in the third complementarity-determining region of the heavy chain (CDR-H3) are rare but naturally encoded in the IGHD germline genes. Here, by panning a phage display library designed based on human germline genes and synthetic CDR-H3 regions against a human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…Given the issue of entropic penalty during peptide binding (60), it seems likely that the constrained structure of CDR-H3 may be an additional important factor in the high-affinity epitope interaction observed for pT231/pS235_1. Indeed, recent studies of human antibody V H (66), shark V NAR (67), and camelid V H H (68) domains with non-canonical cysteines in their CDRs all support the critical role of disulfide bonding in the maintenance of binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the issue of entropic penalty during peptide binding (60), it seems likely that the constrained structure of CDR-H3 may be an additional important factor in the high-affinity epitope interaction observed for pT231/pS235_1. Indeed, recent studies of human antibody V H (66), shark V NAR (67), and camelid V H H (68) domains with non-canonical cysteines in their CDRs all support the critical role of disulfide bonding in the maintenance of binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, folding of the CDR‐H3 can be affected significantly by the presence of pairs of cysteines, which can form disulphide bonds 147. We found that there is some selection against the use of cysteines in central tolerance; the percentage of sequences without any cysteines increases from 85% to 91% between preB and naïve B cells.…”
Section: Cdr3 Characteristicsmentioning
confidence: 86%
“…Contact residues may not always be part of the CDR145 and the same CDRH3 on different heavy/light chain backgrounds can take on different structures 146. As a result of the complexities of protein folding behavior, selection of mutations for affinity may not be directly related to contact residues 147. We looked for any biases in CDR3 properties between different IGHV family genes in our data.…”
Section: Cdr3 Characteristicsmentioning
confidence: 99%
“…The selection of an avian CDRH3 with non-canonical disulfides from E. coli demonstrates not only the capacity to fully access the chicken repertoire but the importance of including such mechanisms of diversity in selection of novel antibody candidates (19,51). The restricted v-gene germ-line repertoire in chicken has evolved mechanisms capable of achieving equivalent levels of Ig protection but is distinct from murine, human, and primate mechanisms and is fully capable of broad range antigen recognition (20).…”
Section: Discussionmentioning
confidence: 99%